REKONSTRUKSI SOSIO-MORAL BERBASIS KITAB TA'LIM AL-MUTA'ALLIM DI PONDOK PESANTREN GEDANGAN DALEMAN KEDUNGDUNG SAMPANG - Muqoffi Muqoffi; Ainun Nafila; Muhammad Zaironi (Pascasarjana Universitas Al-Qolam Malang, 2026)
Education in Indonesia tends to be fragmented into components that operate separately. In fact, there are three types of learning outcomes, cognitive, affective, and psychomotor. Therefore, the teaching of Ta’lim al-Muta’allim should not rely solely on oral instruction, but should involve other approaches that offer stronger potential for optimizing moral practice. On this basis, a study on socio-moral reconstruction grounded in Ta’lim al-Muta’allim was conducted at Pondok Pesantren Gedangan Daleman Kedungdung, Sampang, using a qualitative field research design. The findings indicate that this socio-moral reconstruction is implemented through three approaches. First, a holistic learning process consisting of preparation, introduction of material, active learning, application of knowledge, evaluation, and reflection. Second, moral exemplification through andhep ashor, abekteh, and ngormat, which are elements of Madurese pesantren culture that emphasize commendable conduct in humility, devotion, and respect for others. Third, habituation, namely continuous activities that accustom students to practices with positive value for their patterns of thinking and behavior. The high intensity of these activities leads to internalization, shaping students’ character and manifesting concretely in their daily lives.